Assessment of the impact of the Kansas IDeA Network of Biomedical Research Excellence program on undergraduate participation in research - Chapes, Stephen K.; Velasquez, Sarah E. (My University, 2013)
The Kansas IDeA Network of Biomedical Research Excellence (K-INBRE) was established in 2001 and is a network of 10 higher education institutions in Kansas and northern Oklahoma. The program is funded by the Institutional Development Award (IDeA) program of the National Institutes of Health (NIH). As part of the program’s goal to enhance the research infrastructure in Kansas, a training program was developed to encourage undergraduates to participate in biomedical research. From September of 2002 to May 2012, the K-INBRE supported 731 students at 10 institutions. Although 16% of student participants in the program are still undergraduates, 323 of our students have gone into biomedical graduate school or medical school programs. Thirty-seven percent of all the completed students have matriculated into graduate programs and 19% of our completed students went to medical school. Moreover, 12% have gone into other health-related professions. One percent of our students that went into medical school programs are in highly prestigious M.D./Ph.D. programs. In the fall of 2011, we surveyed participants from the last 10 years about career choices and the impact of the K-INBRE program on those students. Two-hundred twenty-four former and current students responded to the survey with a consensus of high impact of the K-INBRE program on student training, career choices, and perceptions about research.
Keywords: Undergraduate research; Program assessment